If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ln(x) = ln(3) Multiply ln * x 2lnx = ln(3) Reorder the terms for easier multiplication: 2lnx = 3ln Solving 2lnx = 3ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-3ln' to each side of the equation. -3ln + 2lnx = 3ln + -3ln Combine like terms: 3ln + -3ln = 0 -3ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-3 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-3 + 2x)' equal to zero and attempt to solve: Simplifying -3 + 2x = 0 Solving -3 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 0 + 3 2x = 0 + 3 Combine like terms: 0 + 3 = 3 2x = 3 Add '-2x' to each side of the equation. 2x + -2x = 3 + -2x Combine like terms: 2x + -2x = 0 0 = 3 + -2x Simplifying 0 = 3 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4+x-5=5+x-6 | | 3y-1+4y+7=90 | | 9x-3-x=95 | | 4w+8=28 | | 56=2x-7(4x+18) | | X+4=34-4x | | 3q+6=20 | | 6r^2+r=1 | | 26=3x+2x-9 | | x(x+7)+-12(x+7)=0 | | 9x(3x-20)=74 | | 49s^2-81d^2= | | 2(3n-3)=30 | | x(x+11)-18(x+11)=0 | | 9y^2-18y+5=0 | | -19.95+1.10x=18 | | 9y^2-9y+2=0 | | 12-5x-25x^2=0 | | -19.95+1.10x=-1.35 | | u^2+7a^2+6=0 | | 3ln(x+6)=15 | | 2=15z^2+2 | | M+3m+0.5m=36 | | 31n(x-6)=15 | | 81-3x=45 | | 4x+28=30 | | 4w-2w-w+w-w=18 | | 7x-4x-2x-x+x=16 | | 2+3x+1=6x | | 3(2-x)=6 | | 16h+5h-20h=14 | | 7a+a+3a-9a=6 |